THE FUTURE OF LANGUAGE TEACHING: PROSPECTS AND CHALLENGES IN THE ERA OF GLOBALIZATION - Dadajonova Muxtasarxon Farxod qizi,; Karimjonova Shakhlo Ravshanjonovna, (Ustozlar uchun, 2025)
English has become one of the most widely used languages for global communication. With the rapid globalization experienced in recent decades, there is an increasing need for interaction across diverse nations and cultures. This has led to a transformation in the status of English, shifting from being viewed merely as a second language to being recognized as a global language. As English now serves as a tool for both international and intercultural communication, it is crucial to acknowledge the essential connection between language and culture. This transition highlights the move from focusing solely on cultural elements in English as a second language to emphasizing intercultural aspects in English as an international language. Such changes also have significant implications for how English should be taught in this global context.